Novel fluorescence probe for estimation of cysteine/histidine in human blood plasma and recognition of endogenous cysteine in live Hct116 cells - Reddy, Upendar G.; Agarwalla, Hridesh; Taye, Nandaraj; Ghorai, Suvankar; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2014)
A new Cu(II)-complex is used as a ``Turn-On'' luminescence probe for specific detection of endogenous Cys in live Hct116 cells and Cys present in human blood plasma without any interference from other amino acids, especially GSH and Hcy. Difference in the mechanistic pathway for Cys and His recognition is discussed.

Specific probe for Hg2+ to delineate even H+ in pure aqueous buffer/Hct116 colon cancer cells: Hg(II)-eta(2)-arene pi-interaction and a TBET-based fluorescence response - Reddy, Upendar G.; Ramu, Vadde; Roy, Sovan; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2014)
A new molecular probe that demonstrates a distinct TBET process, induced by the Hg(II)-eta(2)-arene pi-interaction, in pure aqueous medium with a large pseudo-Stokes shift of 200 nm.

Fluorescent probe for specific detection of cysteine in the lipid dense region of cells - Ali, Firoj; Anila, H. A.; Taye, Nandaraj; Gonnade, Rajesh G.; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
A new cysteine (Cys) specific chemodosimetric reagent (ER-F) is used in imaging of endogenous Cys localized in the lipid dense region of the live Hct116 cells and the release of Cys within HepG2 cells from a drug following a biochemical transformation. A silica surface, modified with ER-F, could be used for quantitative estimation of Cys present in aqueous solution (pH 7.2) and in a human blood plasma (HBP).

FRET-based probe for monitoring pH changes in lipid-dense region of Hct116 cells - Reddy, Upendar G.; Anila, H. A.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Organic Letters, 2015)
A rhodamine conjugate (L) with a pseudo Stokes shift of 165 nm is used for probing changes in solution pH under physiological conditions. This reagent is found to be nontoxic, and the luminescence response could be used for imaging changes in endogenous pH induced by dexamethanose (DMT) in the endoplasmic reticulum.

New imaging reagents for lipid dense regions in live cells and the nucleus in fixed MCF-7 cells - Ramu, Vadde; Ali, Firoj; Taye, Nandaraj; Garai, Bikash; Alam, Aftab; Chattopadhyay, Samit; Das, Amitava (Journal of Materials Chemistry B, 2015)
Two new uracil (U) and 5-flurouracil (5-FU) labeled ruthenium(II)-polypyridyl based cellular imaging reagents are reported. Confocal laser scanning microscopic images with live and paraformaldehyde (PFA) fixed MCF-7 cells are examined using these two low-cytotoxic reagents. Experimental results show that these two complexes, appropriately functionalized with U (1) and 5-FU (2), have specific affinity for the lipid dense regions like the endoplasmic reticulum, cell membrane, and cytoplasmic vacuoles in live MCF-7 cells, and dye internalization in these regions happened following an endocytosis pathway. Interestingly, these two complexes are found to be localized in the nucleus of the PFA fixed cells. For fixed cells, presumably the lipid layer disruption helped in the explicit localization of the complexes 1 and 2 in the cell nucleus through specific interaction with cellular DNA. Poor and non-specific internalization of an analogous model complex 3, without having a U or 5-FU moiety, reveals the definite influence of U or 5-FU as well as the role of lipophilicity of the respective complex 1 and 2 in the cellular internalization process. Apart from these, a large Stokes shift (similar to 160 nm) and an appreciably long lived (MLCT)-M-3 excited state (similar to 320 ns) in aq. buffer medium (pH 7.4) are other key features for complexes 1 and 2. Unlike the common nuclear DNA staining reagents like DAPI, these low-cytotoxic reagents are found to be highly stable towards photo-bleaching upon irradiation with 455 nm at the MLCT band for these complexes.

New turn on Pd2+-specific fluorescence probe and its use as an imaging reagent for cellular uptake in Hct116 cells - Reddy, Upendar G.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
A new coumarin-rhodamine conjugate is used as a specific probe for Pd2+ ions and this could even delineate Pd(II) from Pd(0) or Pd(IV) in aqueous buffer medium (pH similar to 7). Laser confocal microscopic studies reveal that efficient cellular internalization of this reagent helps in imaging the cellular uptake of Pd2+ as low as 0.1 ppm in Hct 116 cells. This reagent could even be used for estimation of Pd2+ in human urine samples.

Reagent for specific recognition of cysteine in aqueous buffer and in natural milk: imaging studies, enzymatic reaction and analysis of whey protein - Anila, H. A.; Reddy, Upendar G.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
We report a new chemodosimetric probe (L) for specific recognition of cysteine (Cys) in aqueous buffer and in whey protein isolated from fresh cow's milk. Using this reagent we could develop a luminescence-based methodology for estimation of Cys released from a commercially available Cys-supplement drug by aminoacylase-1 in live cells.

Specific reagent for Cr(III): imaging cellular uptake of Cr(III) in Hct116 cells and theoretical rationalization - Ali, Firoj; Saha, Sukdeb; Maity, Arunava; Taye, Nandaraj; Si, Mrinal Kanti; Suresh, E.; Ganguly, Bishwajit; Chattopadhyay, Samit; Das, Amitava (Journal of Physical Chemistry B, 2015)
A new rhodamine-based reagent (L-1), trapped inside the micellar structure of biologically benign Triton-X 100, could be used for specific recognition of Cr(III) in aqueous buffer medium having physiological pH. This visible light excitable reagent on selective binding to Cr(III) resulted in a strong fluorescence turn-on response with a maximum at similar to 583 nm and tail of that luminescence band extended until 650 nm, an optical response that is desired for avoiding the cellular autofluorescence. Interference studies confirm that other metal ions do not interfere with the detection process of Cr(III) in aqueous buffer medium having pH 7.2. To examine the nature of binding of Cr(III) to L-1, various spectroscopic studies are performed with the model reagent L-1 which tend to support Cr(III)-eta(2)-olefin pi-interactions involving two olefin bonds in molecular probe L-1. Computational studies are also performed with another model reagent L-M to examine the possibility of such Cr(III)-eta(2)-olefin pi-interactions. Presumably, polar functional groups of the model reagent L-M upon coordination to the Cr(III) center effectively reduce the formal charge on the metal ion and this is further substantiated by results of the theoretical studies. This assembly is found to be cell membrane permeable and shows insignificant toxicity toward live colon cancer cells (Hct116). Confocal laser scanning microscopic studies further revealed that the reagent L-1 could be used as an imaging reagent for detection of cellular uptake of Cr(III) in pure aqueous buffer medium by Hct116 cells. Examples of a specific reagent for paramagnetic Cr(III) with luminescence ON response are scanty in the contemporary literature. This ligand design helped us in achieving the turn on response by utilizing the conversion from spirolactam to an acyclic xanthene form on coordination to Cr(III).

Cysteine-specific fluorescent switch for monitoring oxidative stress and quantification of aminoacylase-1 in blood serum - Anila, H. A.; Ali, Firoj; Kushwaha, Shilpi; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Analytical Chemistry, 2016)

GSH Induced controlled release of levofloxacin from a purpose-built prodrug: luminescence response for probing the drug release in escherichia coli and staphylococcus aureus - Pal, Suman; Ramu, Vadde; Taye, Nandaraj; Mogare, Devraj G.; Yeware, Amar M.; Sarkar, Dhiman; Reddy, D. Srinivasa; Chattopadhyay, Samit; Das, Amitava (Bioconjugate Chemistry, 2016)
Fluoroquinolones are third-generation broad spectrum bactericidal antibiotics and work against both Gram-positive and Gram-negative bacteria. Levofloxacin (L), a fluoroquinolone, is widely used in anti-infective chemotherapy and treatment of urinary tract infection and pneumonia. The main pathogen for urinary tract infections is Escherichia colt, and Streptococcus pneumoniae is responsible for pneumonia, predominantly a lower respiratory tract infection. Poor permeability of L leads to the use of higher dose of this drug and excess drug in the outer cellular fluid leads to central nervous system (CNS) abnormality. One way to counter this is to improve the lipophilicity of the drug molecule, and accordingly, we have synthesized two new Levofloxacin derivatives, which participated in the spatiotemporal release of drug via disulfide bond cleavage induced by glutathione (GSH). Recent studies with Streptococcus mutants suggest that it is localized in epithelial lining fluid (ELF) of the normal lower respiratory tract and the effective [GSH] in ELF is similar to 430 mu M. E. coli typically cause urinary tract infections and the concentration of GSH in porcine bladder epithelium is reported as 0.6 mM for a healthy human. Thus, for the present study we have chosen two important bacteria (Gram + ve and Gram - ve), which are operational in regions having high extracellular GSH concentration. Interestingly, this supports our design of new lipophilic Levofloxacin based prodrugs, which released effective drug on reaction with GSH. Higher lipophilicity favored improved uptake of the prodrugs. Site specific release of the drug (L) could be achieved following a glutathione mediated biochemical transformation process through cleavage of a disulfide bond of these purpose-built prodrugs. Further, appropriate design helped us to demonstrate that it is possible also to control the kinetics of the drug release from respective prodrugs. Associated luminescence enhancement helps in probing the release of the drug from the prodrug in bacteria and helps in elucidating the mechanistic pathway of the transformation. Such an example is scarce in the contemporary literature.

Specific receptor for hydrazine: mapping the in situ release of hydrazine in live cells and in an in vitro enzymatic assay - Ali, Firoj; Anila, H. A.; Taye, Nandaraj; Mogare, Devraj G.; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2016)
We report a new chemodosimetric reagent capable of detecting hydrazine in the presence of several other competing amine derivatives and ionic analytes of biological relevance. This reagent has been utilized for real time monitoring of in situ N2H4 release during the metabolism of a crucial tuberculosis drug, isoniazid, in live HepG2 cells. The fluorescence response of the reagent based on its specific reaction with N2H4 is used for developing an in vitro assay for aminoacylase-1.

Switch-on NIR probe for specific detection of Hg2+ ion in aqueous medium and in mitochondria - Agarwalla, Hrideshg; Mahajan, Pankaj S.; Sahu, Debashis; Taye, Nandaraj; Ganguly, Bishwajit; Mhaske, Santosh B.; Chattopadhyay, Samit; Das, Amitava (Inorganic Chemistry, 2016)
A new 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY)-based probe molecule (L) is synthesized for specific binding to Hg2+ ion in physiological condition with an associated luminescence ON response in the near-IR region of the spectrum. Appropriate functionalization in the 5-position of each of two pyrrole moieties with styryl functionality in a BODIPY core helped us in achieving the extended conjugation and a facile intramolecular charge transfer transition with a narrow energy gap for frontier orbitals. This accounted for a poor emission quantum yield for the probe molecule L. Binding to. Hg2+ helped in interrupting the facile intramolecular charge transfer (ICT) process that was initially operational for L. This resulted in a hypsochromic shift of absorption band and a turn-on luminescence response with lambda(Em)(max) of 650 nm on specific binding to Hg2+. Observed spectral changes are rationalized based on quantum chemical calculations. Interestingly, this reagent is found to be localized preferentially in the mitochondria of the live human colon cancer (Hct116) cells. Mitochondria is one of the major targets for localization of He2+, which actually decreases the mitochondrial membrane potential and modifies various proteins having sulfudryl functionality(ies) to cause cell apoptosis. Considering these, ability of the present reagent to specifically recognize Hg2+] in the mitochondrial region of the live Hct116 cells has significance.

Photo-induced cytotoxicity and anti-metastatic activity of ruthenium(II)-polypyridyl complexes functionalized with tyrosine or tryptophan - Ramu, Vadde; Aute, Sunil; Taye, Nandaraj; Guha, Rweetuparna; Walker, Michael G.; Mogare, Devaraj; Parulekar, Apoorva; Thomas, Jim A.; Chattopadhyay, Samit; Das, Amitava (Dalton Transactions, 2017)
The synergistic effect of oxygen, light, and photosensitizer (PS) has found applications in medicine for the treatment of cancer through photodynamic therapy (PDT). Induction of apoptosis to cancerous cells will prevent tumor metastasis that spreads cancer cells to the neighboring organs/tissues. Herein, we report the two apoptotic Ru(II)-polypyridyl complexes that are functionalized with pendant amino acid moieties tyrosine (1) and tryptophan (2), respectively. These two water soluble complexes were found to interact strongly (K-a(1) = (1.18 +/- 0.28) x 10(5) M-1 and K-a(2) = (1.57 +/- 0.77) x 10(5) M-1) with CT-DNA. Isothermal titration calorimetry (ITC) studies revealed that these complexes bind to CT-DNA through an entropically driven process. Both the complexes showed photo-induced cytotoxicity and exhibit apoptotic activity under photo-irradiation conditions. The comet assay indicated that these complexes can damage cellular DNA, which is attributed to the significant build-up of O-1(2) level even on irradiation with low intensity light (10 J cm(-2), lambda(Range) 450-480 nm). This photoinduced DNA damage and apoptosis in A549 cells was induced by reactive oxygen species (ROS) and occurred through up-regulation of apoptotic marker caspase-3. Control experiments under dark conditions revealed an insignificant cytotoxicity towards these cells for two photosensitive molecules.